AVALIAÇÃO DA SAZONALIDADE DO ÓLEO ESSENCIAL DAS FOLHAS DE Piper glabratum Kunth - Vitorino, Giuliana Thomas; Cardoso, Claudia Andrea Lima; Caramão, Elina Bastos; Mota, Jonas da Silva (ANAIS DO ENIC, 2014)